2009
DOI: 10.1073/pnas.0812584106
|View full text |Cite
|
Sign up to set email alerts
|

Functional basis of protection against age-related macular degeneration conferred by a common polymorphism in complement factor B

Abstract: Mutations and polymorphisms in complement genes have been linked with numerous rare and prevalent disorders, implicating dysregulation of complement in pathogenesis. The 3 common alleles of factor B (fB) encode Arg ( fB 32R), Gln ( fB32Q), or Trp ( fB32W) at position 32 in the Ba domain. The fB 32Q allele is protective for age-related macular degeneration, the commonest cause of blindness in developed countries. Factor B variants were purified from plasma of homozygous individuals and were tested in hemolysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
85
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 98 publications
(89 citation statements)
references
References 44 publications
3
85
0
1
Order By: Relevance
“…This polymorphic residue is in the Ba fragment of the CFB protein, which does not serve any known function after it is split from CFB by CFD. 23 The polymorphisms are adjacent to the site of enzymatic cleavage and occur in a binding site for C3b during the formation of the proenzyme C3bB. Montes et al, using both human and then recombinant CFB, showed that the 32R variant of CFB binds to C3b with four times stronger affinity than the 32Q variant and formed proenzyme and enzyme more efficiently than the 32Q variant.…”
Section: Genetic Variants Of Complement Genes Associated With Amd Andmentioning
confidence: 99%
See 4 more Smart Citations
“…This polymorphic residue is in the Ba fragment of the CFB protein, which does not serve any known function after it is split from CFB by CFD. 23 The polymorphisms are adjacent to the site of enzymatic cleavage and occur in a binding site for C3b during the formation of the proenzyme C3bB. Montes et al, using both human and then recombinant CFB, showed that the 32R variant of CFB binds to C3b with four times stronger affinity than the 32Q variant and formed proenzyme and enzyme more efficiently than the 32Q variant.…”
Section: Genetic Variants Of Complement Genes Associated With Amd Andmentioning
confidence: 99%
“…The 32W variant formed enzyme at a rate intermediate between the 32R and 32Q variants. 23 The protection against AMD associated with the 32Q variant of CFB is due to less efficient formation of the C3 convertase, a less efficient complement system being advantageous in this context. The findings of the Montes et al study would suggest that the 32W variant should also be protective, though with a less strong effect than 32Q.…”
Section: Genetic Variants Of Complement Genes Associated With Amd Andmentioning
confidence: 99%
See 3 more Smart Citations